Analisis Ayat-Ayat tentang Anjuran Bekerja dan Usaha Ekonomi - Elza Muthia; Syifa Rahma Fadhilah; Muhammad Tajudin (ANWARUL, 2025)
Although studies on work ethics and economic enterprise from an Islamic perspective have grown substantially, research focusing on the application of religious values in contemporary economic practice remains relatively limited. This study aims to explore how the teachings of the Qur’an and its interpretations emphasize the importance of sincere intention, justice, and sustainability in economic activities as integral components of worship and social responsibility. A qualitative approach was employed using library research and textual analysis, focusing on the interpretation of key verses such as QS. Al-Jumu‘ah (62): 9–11 and QS. Al-Mulk (67): 15–17. The findings indicate that religious principles significantly influence the formation of economic practices that are not solely profit-driven but are grounded in justice, divine blessing (barakah), and long-term sustainability. These results enrich the theoretical framework of Islamic economics by underscoring that economic activity should be positioned as a form of worship and a contribution to social welfare. The study recommends the integration of faith-based values in the formulation of modern economic policies and opens avenues for further research on concrete and practical strategies to implement religious principles in economic practice.